Zeigen und Verbergen: Zum Doppelgestus der digitalen Visual Effects im Hollywood-Kino - Kap-herr, Katrin von (transcript, 2018)
Strategies of showing and concealing: a new and overdue exploration of the popular phenomenon of digital visual effects in the movies.